1995
DOI: 10.1016/s0008-6363(95)00136-0
|View full text |Cite
|
Sign up to set email alerts
|

KATP channel modulation in working rat hearts with coronary occlusion: effects of cromakalim, cicletanine, and glibenclamide

Abstract: (i) The anti-ischemic but not the anti-arrhythmic effect of cicletanine may involve opening of KATP. (ii) opening of KATP attenuates, inhibition of the channel exacerbates functional consequences of coronary occlusion, and (iii) KATP opening attenuates reperfusion-induced VF, but it triggers ischemia-induced VF. KATP blocking does not affect VF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
18
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
4
18
0
Order By: Relevance
“…The rat isolated perfused heart has been used extensively to study the pharmacological modulation of arrhythmias. With this model, Ferdinandy et al (1995) demonstrated that a relatively low concentration of the K ATP opener cromakalim, delivered prior to ischaemia, was anti-arrhythmic during reperfusion, despite the fact that higher concentrations caused marked pro-arrhythmia during ischaemia. These findings were consistent with earlier preliminary data that we presented (Workman et al, 1994) from a similar model, but using a different K ATP opener.…”
Section: : Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The rat isolated perfused heart has been used extensively to study the pharmacological modulation of arrhythmias. With this model, Ferdinandy et al (1995) demonstrated that a relatively low concentration of the K ATP opener cromakalim, delivered prior to ischaemia, was anti-arrhythmic during reperfusion, despite the fact that higher concentrations caused marked pro-arrhythmia during ischaemia. These findings were consistent with earlier preliminary data that we presented (Workman et al, 1994) from a similar model, but using a different K ATP opener.…”
Section: : Introductionmentioning
confidence: 94%
“…Reperfusion arrhythmias are also considered to be important clinically, as highlighted by reports of patients in 4 whom serious ventricular arrhythmias occurred shortly after spontaneous relief of episodes of coronary spasm-induced silent ischaemia (Tzivoni et al, 1983), or in whom persistent arrhythmias followed successful thrombolysis (Goldberg et al, 1983), or during reperfusion of the whole heart after a period of surgically-induced ischaemic arrest (Rubin et al, 1985). Despite the potential importance of post-ischaemic reperfusion arrhythmias, the effects of pharmacological K ATP activation on these arrhythmias have been reported infrequently, especially in the absence of arrhythmias during the preceding phase of ischaemia (Ferdinandy et al, 1995; Tosaki et al, 1993; Tanaka et al, 1996). The rat isolated perfused heart has been used extensively to study the pharmacological modulation of arrhythmias.…”
Section: : Introductionmentioning
confidence: 99%
See 3 more Smart Citations